2019
DOI: 10.1007/s10509-019-3646-5
|View full text |Cite
|
Sign up to set email alerts
|

Space weather and hurricanes Irma, Jose and Katia

Abstract: This research is devoted to the determination of the causal relationship between the flow of particles that are coming from the Sun and the hurricanes Irma, Jose, and Katia. To accomplish this, the lag correlation analysis was performed. High correlation coefficients confirmed a preliminary conclusion about the relationship between solar activities and the hurricane phenomenon, which allows further research. Five parameters i.e. characteristics of solar activity (10.7 cm solar radio flux (F10.7), the flows of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Vyklyuk et al [20] underlined the fact that the use of LSTM neural networks allows us to obtain good consideration of the nonlinearity and time delay between input and output factors. Combining these models in the form of ensembles made it possible to significantly increase the accuracy and adequacy of the models in comparison with the approaches described in the research of Hyndman [27] and Radovanović et al [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vyklyuk et al [20] underlined the fact that the use of LSTM neural networks allows us to obtain good consideration of the nonlinearity and time delay between input and output factors. Combining these models in the form of ensembles made it possible to significantly increase the accuracy and adequacy of the models in comparison with the approaches described in the research of Hyndman [27] and Radovanović et al [28].…”
Section: Resultsmentioning
confidence: 99%
“…The data included proton density (p/cc), bulk speed (km/s), and ion temperature (K). The source of data on solar flux F10.7 cm (2800 MHz) was Space Weather Canada [20]. The F10.7 cm solar radio flux (or just F10.7) is, along with the sunspot number, one of the most widely used indices of solar activity [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters represent solar wind and activity variability and are used in previous research. All the parameters used in this study are used in the investigation of dependencies between forest fires and solar activity [59,60], while some of them (IPF > 10 MeV, solar wind, and 10.7 cm radio flux) were used in the research of the relationship between solar activity and hurricanes [10,61]. Since previous research showed that a causal link exists, in this research we attempted to examine if there is a connection between these parameters of solar activity and precipitation-induced floods.…”
mentioning
confidence: 99%
“…Therefore, the monitoring and understanding of spatio-temporal atmospheric changes are important for research in a number of scientific disciplines as well as for geoinformation technologies. Here, first of all, the importance of research into atmospheric changes related to natural disasters should be emphasized (Molchanov et al, 2004;Price et al, 2007;Maurya et al, 2016;Kumar et al, 2017;Vyklyuk et al, 2017Vyklyuk et al, , 2019Manta et al, 2020;Malinović-Milićević et al, 2023). For example, the Lithosphere-Atmosphere-Ionosphere Coupling (LAIC) model based on the effects of ionisation provided by radon released from active tectonic faults before earthquakes is created in Pulinets et al (2022).…”
mentioning
confidence: 99%